Enabling adoption and use of new health information technology during implementation: Roles and strategies for internal and external support personnel. (24th April 2021) - Umstead, Claire N; Unertl, Kim M; Lorenzi, Nancy M; Novak, Laurie Lovett
Abstract: Objective: Successful technological implementations frequently involve individuals who serve as mediators between end users, management, and technology developers. The goal for this project was to evaluate the structure and activities of such mediators in a large-scale electronic health record implementation. Materials and Methods: Field notes from observations taken during implementation beginning in November 2017 were analyzed qualitatively using a thematic analysis framework to examine the relationship between specific types of mediators and the type and level of support to end users. Results: We found that support personnel possessing both contextual knowledge of the institution's workflow and training in the new technology were the most successful in mediation of adoption and use. Those that lacked context of either technology or institutional workflow often displayed barriers in communication, trust, and active problem solving. Conclusions: These findings suggest that institutional investment in technology training and explicit programs to foster skills in mediation, including roles for professionals with career development opportunities, prior to implementation can be beneficial in easing the pain of system transition.